PENGARUH PENGGUNAAN APLIKASI DOMPET DIGITAL TERHADAP POLA PERILAKU KONSUMEN DI MASA COVID-19: PENGARUH PENGGUNAAN APLIKASI DOMPET DIGITAL TERHADAP POLA PERILAKU KONSUMEN DI MASA COVID-19 - thomas anggoro; Retno Purwani Setyaningrum (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
This research discusses consumer behavior in conducting digital payments in buying and selling transactions. Digital payment methods are a new way of making payments, especially during a pandemic like the present, which is also a result of government policies in various countries worldwide to limit outdoor activities and maintain social distance during the Covid-19 pandemic. Consumer behavior has started to shift from conventional payment methods to digital payments. Payment through digital wallets has become popular and widely accepted as an emerging payment method in both developed and developing countries. The objective of this research is to determine the behavior patterns of millennial consumers who tend to make impulsive purchases due to promotions and digital payment facilities. Therefore, the use of digital wallets in the behavior of millennial consumers during the Covid-19 pandemic becomes the research object. This study adopts a qualitative descriptive method with a literature-based approach. Research data is obtained through literature review and theoretical studies from various scientific sources. The research findings indicate that the Covid-19 pandemic has increased the usage of digital wallets due to consumers' inclination towards using electronic transactions that are more suitable and efficient during the pandemic. The digital era has rapidly evolved in a society that has adapted to become adaptive shoppers in a cashless society, developing a new culture known as electronic payment transactions through digital wallets